Quality of energy, energy access and law within the Cuban hydropower context - Peña Pupo, Leonardo; Fariñas Wong, Ernesto Yoel; Luis Cordova, José Grabiel; Delgado Triana, Yanelys (My University, 2020)
This article deals with the quality of energy generated in the autonomous mini and micro hydroelectric plants located in the mountainous regions of Cuba, where they are the only source of energy supply. The quality of energy generated and its availability are a right to the inhabitants of these communities, on an equal footing with those whose supply is through the electricity grid. In this sense, the legal and technical norms existing in Cuba, while defining equality of rights, also impose unviable technical and economic conditions.
Keywords: Cuba; Derecho